35 Medical Complications After Total Ankle Arthroplasty: A Review of the Evidence. (19th August 2022) - Curlewis, K; Leung, B; Sinclair, L; Chan, G; Bendall, S; Ricketts, D
Abstract: Aim: Total Ankle Arthroplasty (TAA) is increasingly being undertaken globally for the treatment of end-stage ankle arthritis. For each TAA procedure informed consent is required. This requires disclosing all material risks that the patient may find significant. The consent process should include discussion of all relevant complications, both medical and regional. There is a lack of data regarding the medical complications of TAA. This might cause problems in obtaining valid informed consent. Methods: A literature review was performed. The medical complications and mortality rate of TAA were identified and summarised. Results: The average rate of systemic medical complications after TAA was 3% (range: 0% - 7%). The average mortality rate following TAA was 0.3% (range: 0% - 0.72%). The following risk factors were identified for medical complications: obesity, diabetes, systemic co-morbidities, preoperative blood transfusion, revision procedures, and long anaesthetic duration. Conclusions: As part of obtaining informed consent for TAA, the medical complication rate of 3% and mortality rate of 0.3% ought to be included, documented, and conveyed to patients alongside the regional complications.